A QUALITATIVE EVALUATION OF A POSITIVE REAPPRAISAL INTERVENTION FOR HOSPICE CAREGIVERS. (20th December 2022) - Cho, HanNah; Demiris, George; Oliver, Debra Parker; Washington, Karla
Abstract: For older adults who receive hospice services in the United States, family members often become their primary caregivers playing an essential role in delivering care. Nearly 25% of hospice patients and families report the need for improved communication and additional emotional support. However, there are few interventions targeting specifically caregivers. Whereas the term caregiving implies a unidirectional flow of benefits from the caregiver to the care recipient, caregivers also experience emotional, cognitive, behavioral, or interpersonal rewards from caring for a loved one. Research has demonstrated that positive gains are common among caregivers, often manifested with negative experiences. Positive reappraisal, a form of emotion-focused coping, is especially relevant when dealing with intractable stressors. Positive reappraisal is supplemental to problem-solving therapy interventions, yet this component has never been tested in a hospice setting. In this study, we wanted to understand hospice caregivers' impressions of a problem-solving therapy intervention enhanced with positive reappraisal modules (called PISCESplus). We conducted a qualitative study examining hospice caregivers' perceptions of positive reappraisal. Participants received the intervention (as part of a larger clinical trial). Caregivers' exit interviews were audio-recorded and transcribed. Thirty hospice caregivers' interviews were analyzed. Many participants reported a paradigm shift in their thought processes. Positive reappraisal helped them reframe negative emotions to positive ones, declutter their minds, and acknowledge that caregiving required work and effort. Study findings demonstrate the potential of this intervention to improve the coping skills of caregivers in the hospice setting.